Is Mask Ventilation an Acceptable Alternative to Endotracheal Intubation for Pregnant Women Undergoing ECT? [A162]. (May 2022) - Jhaveri, Vasanti; Martinez, Ramon; Trippensee, Arvin; Roussos-Ross, Dikea (Kay); Brennan, Meghan; Wendling, Adam
Abstract : INTRODUCTION: Electroconvulsive therapy (ECT) is an evidence-based treatment for severe depression and bipolar disorder in pregnancy. ECT involves induction of general anesthesia with muscle relaxation requiring positive-pressure ventilation. Airway manipulation may lead to complications such as vocal cord injury, aspiration, inability to ventilate, and death. Appropriate airway management for ECT in pregnant patients is unknown. The purpose of this study was to determine if there are differences in incidence of airway complications (AWC) in subjects who underwent mask ventilation (MV) versus endotracheal intubation (ETI). METHODS: This was a retrospective case-control study conducted from June 1, 2011, to June 30, 2020, of all adult pregnant patients who underwent anesthesia for ECT. Each ECT treatment on a pregnant patient was matched with two ECT treatments in nonpregnant control patients. Charts were queried for airway management (MV versus ETI), gestational age, and AWCs. Each ECT procedure was considered an independent airway event. RESULTS: A total of 13 nonpregnant and 11 pregnant patients met inclusion criteria and received 154 and 76 ECT treatments, respectively. Of the 76 ECT treatments in pregnant patients, 12 occurred in the first trimester, 44 in the second trimester, and 20 in the third trimester. In pregnant patients, airway management consisted of MV in 57 of the 76 treatments: 12 in the first trimester, 33 in the second trimester, and eight in the third trimester. No airway complications were experienced in pregnant or nonpregnant patients. CONCLUSION: There were no airway complications observed in pregnant patients undergoing either MV or ETI regardless of gestational age. Our data supports consideration of less invasive airway management during ECT of pregnant patients.